KONTROL KUALITAS AIR UNTUK BUDIDAYA IKAN LELE PADA SISTEM TANAM AQUAPONIK - Yusuf Rangga Pratomo; n/a Nurussa’adah; Raden Arief Setyawan (Jurnal Mahasiswa TEUB, 2023)
The process of fish farming is a technical activity that requires certain knowledge and expertise, fish farming is also a type of business that is in great demand by the public because it has high profit margins. Aquaponics is a planting method in which plants grow in water. Now, due to the depletion of planting land, people use the method of cultivating fish in aquaponic systems. Often beginners in cultivation encounter problems during the cultivation process due to a lack of knowledge and technical level in handling the problems encountered such as the large number of dead fish and dry or rotten plants. These problems arise due to unsuitable environmental conditions for the growth and development of fish and plants. Therefore, certain control methods are needed so that environmental conditions will always be good for the growth and development of fish and plants or also called ideal cultivation conditions. Control methods will regulate water parameters such as pH, ammonia and temperature to be beneficial during the cultivation process. With the application of this method, ideal conditions will always be maintained, so that problems such as fish seeds that die easily, rotting plant roots, and dry plant leaves can be minimized or even not arise. Keyword: aquaponic, fish cultivation, control method, monitoring, water parameter.